African languages as medium of assessment in the teaching of indigenous languages in higher education: a paradigm shift - Viriri, Eunitah; Ndimande-Hlongwa, Nobuhle (Journal for Language Teaching, 2023)
This study was a call for a paradigm shift in the language of assessment for indigenous languages in higher education. It challenged the continued use of English in Teaching Practice supervision at one Zimbabwean State University whose language policy emphasises the teaching of African languages through the respective languages. It sought to establish challenges encountered by students studying African languages who are taught and examined through indigenous languages in all the other modules except for Teaching Practice. This research used the qualitative paradigm where ten randomly selected student teachers practicing ChiShona were interviewed together with two section coordinators. Document analysis was also used to analyse assessment reports. From the study, it was established that the English instruments were designed to accommodate supervisors who are not indigenous languages specialists, there was confusion among supervisors and supervisees on translating indigenous languages on documents and used during lesson delivery to English and vice versa and the student teachers’ potentials were limited due to difficulties in interpreting the instrument. The study concluded that the use of English in teaching practice for African languages was not effective as it compromised quality in both practice and supervision. It, therefore, recommends the use of assessment instruments prepared in indigenous languages.